A rational design for a once through thermophilic anaerobic digestion of palm oil mill effluent - Wong, Kien Keong; Muhammad Zain, Omar; Abdullah, Ramdzani (Institution of Engineers, Malaysia, 1980)
Thermophilic anaerobic digestion on palm oil mill effluent (POME) was carried out at 5sOC in four reactors with retention times of 5, 15, 25, and 35 days on a laboratory scale to evaluate the biokinetic coefficients, pollution abatement and gas generation. The biokinetic coefficients Y, k, Ks, kd were found to be 0.89, 0.49 day-' 1500 mg/litre and O. 17 day 1 respectively. The analyzed supernatant liquid from 8-hour column settlings of the homogeneous reaction mixtures revealed that the Division of Environment's fourth-generation standards can all be satisfied with a retention time of 35 days. Only total solids did not meet the fourth-generation standards at 25 days' retention time. Gas generation capacities of 0.31, 0.72, 0.96 and 1.02 m3/kg volatile solids fed for the 5, 15, 25 and 35 days' retention time reactors were prolific when compared with those of other biological feed materials.